Da Amazônia a Angola: narrativas de selva e o testemunho em geografias periférica - (:unkn) unknown (Universidade Federal do Amazonas, 2013)
The theme of this dissertation is set on the interface between literature and memory, electing the Testimony theoretic perspective, for the critical appraisal of the novels A Selva (1930), by the writer José Maria Ferreira de Castro, and Mayombe (1980), by Pepetela. The scope of this research is to carry out a comparative analysis of the novels on spot, from a theoretic approach which makes a reading of the narratives as a testimony of the barbarism in the geographic-historic contexts in the agenda: Amazonia and Angola. Initially, the focus is on the study of the personal archives representation and on their implication on the aesthetic creation process, pointing out how authorship, biographic subject and traumatic and/or political experience interweave, not only Castro and Pepetela‟s literary writing, as well as the critical production about their novels. The second part (made of the two last chapters) analyze the discourses, the social types and the natural (and cultural) spaces representations in the literary contexts studied, thinking on the limits of the language when dealing with experiences of violence and subjugation in isolated, forestry geographies and historically steeped in preconceived ideas.
Keywords: Literaturas de língua portuguesa; Amazônia; Angola; Testemunho; Natureza; Violência.; Portuguese language literatures; Amazonia; Angola; Testimony; Nature; Violence; LINGUÍSTICA, LETRAS E ARTES: LETRAS